Comparison of three conventional PCR test (Bulman & Marshall, 1997) versions for the molecular identification of Globodera pallida and G. rostochiensis cysts and juveniles. (April 2014) - van de Vossenberg, B. T. L. H.; Voogd, J. G. B.; Westenberg, M.; Karssen, G.
<x xml:space="preserve">Abstract</x> Three different versions of the conventional PCR described by Bulman & Marshall (1997) for the identification of cysts and juveniles of Globodera pallida and G. rostochiensis were compared: the original Bulman & Marshall, Bulman & Marshall as described in EPPO PM 7/40 (2) and an in‐house modified version of the Dutch National Plant Protection Organization (NPPO‐NL). The versions differ from each other in thermocycler conditions and primer sequences. Two different polymerases (Invitrogen and Roche) were assessed using the different test versions, and performance criteria analytical sensitivity and analytical specificity were determined. Roche‐based reaction mixes had the highest amplicon yield and were used for further comparison of the different test versions. The different test versions performed equally well in terms of analytical specificity. No false positive or false negative results were observed. The test version NPPO‐NL proved to be the most sensitive test version with a limit of detection of 1 juvenile for both G. pallida and G. rostochiensis.